Autochthonous Starter Effect on the Microbiological, Physicochemical and Sensorial Characteristics of Moroccan Goats Milk Cheeses - El Galiou, Ouiam; Antonio Centeno, Juan; Zantar, Said; Bakkali, Mohammed; Carballo, Javier; Laglaoui, Amin (JOURNAL OF ADVANCES IN BIOTECHNOLOGY, 2014)
The effect of adding four Lactococcus lactis subsp. Lactis, Lactococcus lactis subsp. lactis Bv. diacetylactis and Lactobacillus paracasei autochthonous strains as single starters (A and B) on the microbiological, physicochemical and sensory characteristics of Moroccan goats milk cheese was investigated. Batches with a commercial starter (C) and with raw goats milk without starter (D) were also made as controls. The results indicated that the different starter cultures used significantly affected the compositional characteristics of Moroccan goats cheese. At the first day of ripening, the pH values of cheeses manufactured with any type of starter were significantly higher than those made without starter. No significant differences (P >0.05) in values of total solids (T.S.), proteins, ash, FAT and lactose content were found between any of the batches after 7 days of ripening. The autochthonous starters in Moroccan cheesemaking were successful at reducing the levels of coliforms earlier in ripening than in cheeses made without starter and even in those made with the commercial starter. These results suggest that the combined activity of L. Lactis subsp. lactis, L. Lactis. subsp. Lactis bv. diacetylactis and L. paracasei, produces cheese with good sensory characteristics.